Calculation of standard bodyweights for dogs, cats, rabbits, and guinea pigs - Stuart D. Becker; Dan G. O’Neill; Siân-Marie Frosini; Laura E. Stapleton; David M. Hughes; Dave C. Brodbelt (PLoS ONE, 2025)
Standard bodyweights are an essential component of calculations that summarise many population-level measures in companion animals, including the defined daily doses for veterinary species (DDDVet) reporting antimicrobial usage. Standard species bodyweights may originate from data derived from clinical records, but current methods to obtain these values risk inaccuracy because they exclude measurements obtained from juvenile animals and consider only individuals that have achieved stable adult bodyweight. This study aimed to improve the accuracy of standard population level species bodyweights through the development of a prediction modelling approach to estimate point mean population bodyweight in dogs, cats, rabbits, and guinea pigs. Data were obtained from the VetCompass database and included bodyweight measurements from approximately three million dogs, two million cats, 220,000 rabbits and 62,000 guinea pigs across 1,800 veterinary practices in the United Kingdom. Initially, Loess models were used to identify the age at which juvenile animals transitioned from growth to stable adult bodyweight. Linear mixed effects models were developed to predict juvenile growth, calibrated such that predicted cessation of growth matched that observed in the Loess models. The prediction models were then used to adjust bodyweight measurements obtained from clinical records of juvenile patients, allowing historical measurements to be included for estimation of a point mean population bodyweight on a subsequent specified target date. Juvenile growth transitioned to stable adult bodyweight at approximately 14 months in dogs, and 13 months in cats, rabbits, and guinea pigs. Point mean whole-population bodyweights estimated on 31st December for each year 2014 – 2023 found that the mean bodyweight of cats, rabbits, and guinea pigs was approximately 4.2 kg, 2.3 kg, and 1.0 kg respectively and changed little over this time period. However, dogs showed a trend to lower mean bodyweight over time, with a mean value of 17.6 kg in 2014, reducing to 16.1 kg by 2023.